IMPLEMENTASI VLAN DAN SPANNING TREE PROTOCOL (STP) DENGAN MENERAPKAN PROTOKOL INTERNET IPv6 - , SARITA ANINDITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The reliability of a network in the data transmission is very important for industry. Network redundancy is required to maintain the stability of the network itself. However it will cause looping which may interfere with the connection to a network. In order to overcome the problem of looping, this study aims at designing a network redundancy topology that can prevent loops by implementing VLAN and using Spanning Tree Protocol (STP) technique and implements IPv6 addressing. In this study, the STP types that are used are PVST+ and Rapid-PVST +. The common STP is not used because it is not adequate to solve convergence problem in terminating a link or a device failure. Due to this fact, other types of STP such as PVST+ and Rapid â PVST+ using IPv6 are developed. IPv6 is used because of the limited number of IPv4 addresses. The implementation also includes the use of VLAN technology because the designed network is mostly implemented using switch devices. The primary use of this network is to use VLANs and is designed using hierarchical topology. The implementation of PVST+ and Rapid-PVST+ are proven to solve looping problems that may occur. VLAN implementation works well which is characterized by the ability of devices with different VLANs to communicate with each other. Rapid-PVST + is also proved to be 40 times faster in the convergence, if there is a failure in a link. Keywords: Spanning Tree Protocol (STP), PVST+, Rapid-PVST+, IPv6, VLAN